The athletic skills track: Age- and gender-related normative values of a motor skills test for 4- to 12-year-old children - Hoeboer, J.J.A.A.M.; Ongena, G.; Krijger-Hombergen, M.; Stolk, E.; Savelsbergh, G. J. P.; de Vries, S. I. (Journal of Science and Medicine in Sport, 2018)
Objectives: The aim of the presented study is to provide age- and gender-related normative values and MQ values for a motor skills test, the Athletic Skills Track, among 4- to 12-year-old children. Design: Cross-sectional. Methods: In 2016, a total of 7977 Dutch children, 4036 boys (mean age 8.6 years, SD 2.1) and 3941 girls (mean age 8.6 years, SD 2.1), performed an age-related version of the Athletic Skills Track (AST). The AST is a track consisting of 5-7 fundamental movement skill tasks that should be completed as fast as possible. The children performed the test during a regular physical education (PE) lesson under the supervision of their own PE teacher. For each version of the AST (AST-1: n = 917; AST-2: n = 3947; AST-3: n = 3213) age- and gender-related reference centiles were derived from the gathered data using the Lambda, Mu, Sigma (LMS) method. Results: All children completed the AST within 60 s (mean 29.6 s, SD 7.7). An independent samples t-test showed that boys were significantly faster in completing the track than girls, except for the 4-year-old boys. Therefore, age- and gender-related reference centiles were derived. The reference curves demonstrate an almost linear decrease in time to complete AST-1 and AST-2 with increasing age. Conclusions: The present study provides age- and gender-related normative values and MQ values for the AST among 4- to 12-year-old Dutch children. With these normative values PE teachers can interpret children`s performance on the AST.